Naskah Ulu MNB 07.55: Wacana dan Praktik Sosial Begadisan pada Kelompok Etnik Serawai di Bengkulu - Sarwit Sarwono (Manuskripta, 2017)
This research aims to disscuss about Ulu MNB 07.55 manuscript related to social practice of begadisan in Serawai ethnic group of Bengkulu. The research based on text as discourse, that is knowledge about social practices, of how things are or must be done, together with specific evaluations and legitimations of, and purposes for, these practices. Based on codex data, known that MNB 07.55 manuscript derived from Serawai ethnic group of Bengkulu, written approximately in the mid-twentieth century. At that time (even until today), the social practice of begadisan still carried out intensively by the ethnic. Furthermore, this manuscript containts a dialogue between unmarriage bachelors and girls. In this connection, the writing of this manuscript is not intended as a record of events begadisan objectively, but is intended as the construction of knowledge about the practice of begadisan that it contains a certain value and legitimacy of identity and social functions of the author of the text. In the context of writing, the manuscript can be seen as a re-contextualization begadisan practice. --- Penelitian ini bertujuan untuk mendiskusikan tentang Ulu MNB 07.55 yang berkaitan dengan paktik-praktik sosial begadisan di Serawak, salah satu etnis Bengkulu. riset ini berdasarkan diskursus teks naskah tersebut yang memuat pengetahuan tentang hal itu, bagaimana sesuatu yang harus diselesaikan beserta evaluasi yang spesifik, legitimasi, dan tujuan ritual tersebut dilakukan. Berdasarkan naskah tersebut, diketahui bahwa MNB 07.55 berasal dari etnis Serawai, Bengkulu, ditulis kira-kira pertengahan abad ke-20. pada masa itu sampai hari ini, praktik-praktik sosial begadisan tetap dilestarikan dengan baik oleh etnis tersebut. Lebih lanjut, naskah ini memuat dialog antara lelaki perjaka dengan gadis yang hendak disuntingnya. Dalam relasinya, penulisan manuskrip ini tidak hanya merekam aktivitas begadisan semata, melainkan juga membangun pemahaman tentang nilai-nilai legitimasi identitas dan fungsi sosial yang terdapat pada ritual begadisan yang terdapat pada teks naskah ini. Dalam konteks penulisan, naskah ini juga dapat ditinjau sebagai pengembalian konteks ritual begadisan.